PENGARUH FREE CASH FLOW, BOARD SIZE, DAN KARAKTERISTIK PERUSAHAAN TERHADAP MANAJEMEN LABA - Lavina, Stefani Grimonia; Destriana, Nicken (E-Jurnal Akuntansi TSM, 2023)
Profit is one of the information that is quite noticed by users of financial statements such as investors and creditors because it can describe the performance of a company. The importance of the profit figure triggers management (as the party who has the opportunity and control) to carry out earnings management practices. Therefore, it is necessary to understand what factors can affect earnings management so that the decision-making process in business can be carried out correctly. The purpose of this research is to obtain empirical evidence related to the factors that can affect earnings management that is the influence of firm size, financial leverage, firm age, profitability, board size, free cash flow, and sales growth on earnings management. This research is causality and uses secondary data sources, with the research population being manufacturing companies listed on Indonesia Stock Exchange from 2019 to 2021. The amount of sample obtained and used are 76 companies with sampling technique that is purposive sampling method. The data obtained were then analyzed using the multiple linear regression method. The results of this research indicate that financial leverage and profitability have a positive effect on earnings management, while firm age and free cash flow have a negative impact on earnings management. The company size, board size, and sales growth have no effect on earnings management.